Development of Collaboration Script-Based Worksheets to Improve Collaborative Skills and Learning Outcomes in Junior High Schools Science Learning - Dwipoyanti, Nur Atmi; Supeno, Supeno; Nuha, Ulin (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
Science learning is expected to be capable of various competencies following curriculum demands, including students' collaborative skills. Collaborative skills provide many benefits to students. However, the facts show that the collaborative skills achieved by students in current learning are still low because the learning process is not directed at achieving the desired targets. Thus, this research was conducted to develop a collaboration script-based worksheet to improve junior high school students' collaborative skills and learning outcomes in science learning. This type of research is development research, which is carried out in three stages: the preliminary research phase, the development and prototyping phase, and the assessment phase. The research results show that the collaboration script-based worksheet developed in this research is categorized as valid, practical, and effective. Thus, it can be said that collaboration script-based worksheets can help students learn science collaboratively to improve collaborative skills and student learning outcomes.